Changes in the Organzational of the Environmental Agency of the City of Ternate North Maluku Province - Arifin, Mahar (International Journal of Psychosocial Rehabilitation, 2020)
Environment Life Agency (BLH) in Ternate City in the performance of duties and their responsibility not run as mandated by the legislation in environmental management from planning, hendling up evaluation, and prevention. This condition indicates that the change of the District Enverionment Life Agancy Organization (BLH) in Ternate City beyond expectation and not according to the specifications within the county that results in the execution of the task is not already running. By looking at the various issues that arise, this study is capable of an analysis done on the change of the District Enverionment Life Agancy Organization (BLH) in Ternate City, North Maluku. This research is expected to discover a new concept of change organizations in developing knowledge of public administration. This study uses a qualitative approach as it aims to gain an understanding of empirical phenomena that is intact in the meaning contained in the problem of organizational change. Researchers as the main instrument, and data obtained through direct observation in the study site. Depth interviews with informants while the data were analyzed descriptively qualitative.My study found that organizational change Environment Agency (BLH) territory of North Maluku Province has not fully taken into account aspects of human resources, job descriptions, organizational strategy, organizational design, use of technology, and culture. Thus, the concepts found in this study are that the strengthening of human resources determines the success of organizational change, which is reflected in the solidity of the structure, duties, and working strategies of local government organizations.